Hyperalgesia syndrome in animals and methods of its treatment according to experimental data and morphometry - Dmytriiev, Dmytro (ScienceRise: Medical Science, 2017)
Aim. The assessment and choice of analgesia method relative to hyperalgesia development in the experiment. Methods. Antiflogogenic effect of preparations was studied on the model of caragenin edema in 147 white non-linear rats with the mass 120–150 g. As a hyperalgesia model was used a caragenin edema. It was reproduced by the subplantar administration of 0,05 ml of 1 % caragenin solution in the right back extremity of the animal. Results. The combined use of bupivacaine regional analgesia manifested the moderate antiflogogenic effect (AFA was 25,3, 20,9 and 11,6 %, respectively), whereas fentanyl administration is, on the contrary, associated with the growth of prostaglandin edema. The conducting anesthesia with bupivacaine led to the more expressed analgesic effect that was proved by the level of corticosterone in blood. In 5th group (bupivacaine) the corticosterone level was 102,8±8,1 ng/ml that is 2,5 times less than in 2 one (fetanyl) and in 3 group (ketamine) (р<0,05) Conclusion. The complex study of reactions of pain behavior, physiological rates and laboratory stress tests demonstrated that the use of bupivacaine conducting anesthesia led to the more expressed analgesic effect